A Nuclear Ban Treaty: prospects and issues. Issue 7 (8th August 2016) - Unknown
Abstract : The United Nations General Assembly is expected soon to authorise the negotiation of a treaty that would make nuclear weapons illegal. Despite little media attention, prospects for an actual agreement look better this time. Countries possessing nuclear weapons have resisted the idea and would continue to do so. But with nuclear arms control on other fronts stalled, the negotiation of a Ban Treaty may be the only game in town for some time.